Book Review: The Principles of Good Corporate Governance and Law Enforcement - Mustofa, Imam (Millah: Journal of Religious Studies, 2007)
Title : Penerapan Good Corporate Governance (Mengesampingkan Hak-hak Istimewa Demi Kelangsungan Usaha) Writer : Indra Surya & Ivan Yustiavandana Publication : 2006 Publisher : Kencana Pages : xii + 243 pages